2010
DOI: 10.1007/s00268-010-0908-3
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Associated with the Treatment of Gallstone Disease: A 10‐Year Contemporary National Experience

Abstract: Although cholecystectomy is a relatively safe procedure, patients who die as a result of gallstone disease tend to be elderly, to have been admitted as emergency cases, and to have had co-morbidities. Future combined medical and surgical perioperative management may reduce the mortality rate associated with gallstones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
1
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 32 publications
4
18
1
5
Order By: Relevance
“…While it appears that gross mortality rates exceed today's standards, the authors believe that the subgroup of patients with high ASA scores require separate consideration: Most fatalities in our study were attributable to nonsurgical complications such as perioperative myocardial infarction or congestive heart failure typically seen in ASA score III and IV patients. Similar to our and the aforementioned Scottish trial [24], Murphy et al [23] could demonstrate that advanced age, comorbidities and male gender are key factors associated with in-hospital complications in their analysis of 1,102,071 LC patients. In fact, Melloul et al in their comparison of percutaneous drainage vs. emergency LC in acute cholecystitis in critically ill patients found mortality rates of 13% (drainage) and 16% (LC), highlighting the potential risks in this vulnerable group of patients [25].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While it appears that gross mortality rates exceed today's standards, the authors believe that the subgroup of patients with high ASA scores require separate consideration: Most fatalities in our study were attributable to nonsurgical complications such as perioperative myocardial infarction or congestive heart failure typically seen in ASA score III and IV patients. Similar to our and the aforementioned Scottish trial [24], Murphy et al [23] could demonstrate that advanced age, comorbidities and male gender are key factors associated with in-hospital complications in their analysis of 1,102,071 LC patients. In fact, Melloul et al in their comparison of percutaneous drainage vs. emergency LC in acute cholecystitis in critically ill patients found mortality rates of 13% (drainage) and 16% (LC), highlighting the potential risks in this vulnerable group of patients [25].…”
Section: Discussionsupporting
confidence: 90%
“…Mortality was higher in urgent (1%) than elective LC (0.3%) and was to our surprise not associated with surgeons' experience. Furthermore, mortality in urgent LC decreased from 1.6% in 1999 to 0.6% in 2009, a figure that compares well to a recent large Scottish study by Scollay et al, in which mortality in urgent LC dropped from 1.3% in 1997 to 0.55% in 2006 [24]. While it appears that gross mortality rates exceed today's standards, the authors believe that the subgroup of patients with high ASA scores require separate consideration: Most fatalities in our study were attributable to nonsurgical complications such as perioperative myocardial infarction or congestive heart failure typically seen in ASA score III and IV patients.…”
Section: Discussionsupporting
confidence: 83%
“…Although LC is a relatively safe procedure, patients who die as a result of gallstone disease tend to be elderly patients, to have been admitted as emergency cases, and to have had multiple comorbidities (30). Deaths following cholecystectomy usually followed emergency admission (76%) and were more likely to have been associated with postoperative medical complications than surgical complications (30). Our results from the study hospital indicated that fatal outcome of LC was rare, and also postoperative complications remained at acceptable level.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, we lost 4 of our patients, 3 males and one female, giving a mortality rate of (2%), however, these mortalities were not due to technical errors or medical mistakes, Three of the 4 mortalities were patients already had cardiovascular diseases and were on treatment, the other one case.had a pulmonary embolism despite the low dose of low molecular weight Heparin therapy, however, (Scollay et al, 2011;Agabiti et al, 2013;Sandblom et al, 2015) No iatrogenic injury to the main vessel or bowel injury was reported. Furthermore, no CBD injury was reported.…”
Section: Mortalitymentioning
confidence: 89%